Building Moral Intelligence with Cooperative Learning in Elementary School (Universitas Negeri Semarang, 2023)
Dealing with the negative impacts of socio-cultural changes in the 5.0 era requires moral intelligence for elementary school students. This study aims to obtain qualitative data on the process of developing moral intelligence in learning using cooperative learning. The method uses qualitative ethnography with research implementation procedures referring to Wiersma Jurs with the stages of identifying phenomena, formulating research questions, identifying subjects, collecting data, analyzing data, and making conclusions. Data collection techniques use observation, interviews, and document analysis. The research subjects consisted of 26 students in grade 5 elementary school PGSD FIP Laboratory UNJ and Budi Wanita Elementary School Jakarta for data triangulation. The results of the study determined that students were able to develop moral intelligence that is empathy, tolerance, respect, justice, and self-control through learning civic education using cooperative learning. Activities to make a mind map, make group tasks, and games through the process of interacting while working in a group trains. The novelty is that the uniqueness of the students who are the subjects of the study have a diversity of abilities. In an inclusive classroom using civic learning based on cooperative learning could be trained to develop moral intelligence. The benefits of research can provide examples of the implementation of civic education learning with cooperative learning to develop moral intelligence.